Emerging role of extracellular vesicles in veterinary practice: novel opportunities and potential challenges - Xiong, Yindi; Lou, Peng; Xu, Chuang; Han, Bo; Liu, Jingping; Gao, Jian (Frontiers in Veterinary Science, 2024)
Extracellular vesicles are nanoscale vesicles that transport signals between cells, mediating both physiological and pathological processes. EVs facilitate conserved intercellular communication. By transferring bioactive molecules between cells, EVs coordinate systemic responses, regulating homeostasis, immunity, and disease progression. Given their biological importance and involvement in pathogenesis, EVs show promise as biomarkers for veterinary diagnosis, and candidates for vaccine production, and treatment agents. Additionally, different treatment or engineering methods could be used to boost up the capability of extracellular vesicles. Despite the emerging veterinary interest, EV research has been predominantly human-based. Critical knowledge gaps remain regarding isolation protocols, cargo loading mechanisms, in vivo biodistribution, and species-specific functions. Standardized methods for veterinary EV characterization and validation are lacking. Regulatory uncertainties impede veterinary clinical translation. Advances in fundamental EV biology and technology are needed to propel the veterinary field forward. This review introduces EVs from a veterinary perspective by introducing the latest studies, highlighting their potential while analyzing challenges to motivate expanded veterinary investigation and translation.